Current Research and Patents of Plant Fiber Composites - Wang, Jiankang; Li, Zhijian; Lu, Hongwei (Recent Patents on Mechanical Engineering, 2019)
Background: With the improvement of environment protection awareness, human beings have gradually become aware of that the plastic products, waste are harmful to the human living environment. Therefore, research and application of biodegradable materials that do not rely on petroleum resources have become hot topics. Researchers have accelerated the development and promotion of plant fiber because they are good flexibility, relatively rough surface and biodegradable. Objective: The development of plant fiber composites is reviewed, including composition ratio, interfacial modification, processing technology, and the effects of these technologies on the properties of plant fiber composites. Methods: The paper reviews various patents and research developments about plant fiber composite materials. It also analyzes the advantages and disadvantages of various patents and technologies from the aspects of biodegradable ability, mechanical properties, dispersing performance, processing properties, cost, and so on. Results: The component proportion, interface modification, and processing technology of plant fiber composite materials are prospected to improve the quality and application of the plant fiber composite materials in the future development. Conclusion: The considerable attention has been paid on the technology of biodegradable plant fiber composite. The recent patents and technologies have shown us a wider application in biodegradable plant fiber composite. The problems how to improve the mechanical properties of plant fibers, the dispersion properties of plant fibers and resins, and the processing properties of composite materials, will need more and more methods and equipment to solve or simplify.
Keywords: modification